Takdir Perspektif Masyarakat Desa Srijaya Baru Ogan Komering Ilir (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2021)
This study aims to determine destiny in the community perspective of Srijaya Baru Village, Air Sugihan District, Ogan Komering Ilir District. The people of Srijaya Baru Village in understanding destiny are real things in life but there are also different opinions regarding the problem of destiny. The formulation of the problem in this research is 1. How is destiny in the view of Islam 2. How is the view of the people of Srijaya Baru Village to understand destiny. This type of research is field research field research. Sources of data used in this study are primary data and secondary data. The primary data sources are village heads, religious leaders and community leaders in Srijaya Baru Village. And secondary data is in the form of literature and documents related to this research in the form of books, journals, articles and the internet and analyzed using qualitative destcriptive techniques with a sample of 30 interviews. Based on the results of this study, it can be concluded thad destiny in the perspective of the people of Srijaya Baru Village, Air Sugihan District, Ogan Komering Ilir Regency. Happens is like there is a community who feels anxiety. Disappointed, complained about the problems he was experiencing. There are those who are grateful, endeavor and pray with the destiny that Allah has given, but there are also those who feel hopeless about what Allah has destined. Allah has given a way for humans to be able to change their destiny from bad to good from unsuccessful to successful, all of that is the will of Allah or it can be called the destiny of Allah. But god commands humans to stive in order to achieve their life goals. Allah Almighty created everything including creating human destiny. Keywords: Destiny, Faith, Fate